WHAT IS CRITICAL COMMUNITY PSYCHOLOGY? - Frizelle, Kerry (PINS-Psychology in Society, 2025)
Duncan, N, Bowman, B, Naidoo, A, Pillay, J & Roos, V (eds) (2007) Community psychology: Analysis, context and action. Cape Town: UCT Press. ISBN 978-1-919-71397-7. Pages xv + 463. As a critical psychologist I aim to introduce students registered for my community psychology module to a critical approach to community psychology. I aim to demonstrate that there is an alternative to mainstream psychology and that, more specifically, there is an alternative to mainstream community psychology. In 2005 Nelson and Prilleltensky edited a text entitled Community psychology: In pursuit of liberation and well-being. This text provides an excellent outline to a critical approach to community psychology. It proved, however, to be too long and detailed to cover in a module that is a term long and because it is internationally published is an expensive option to prescribe in the South African context. I have, therefore, largely relied on locally published community psychology texts when teaching my module. While these books may not be specifically focused on a critical approach, many of the texts are critically orientated.